A Turn to the African Girl. Issue 1 (1st March 2023) - Jaksch, Marla L.; Fourshey, Catherine Cymone; Moletsane, Relebohile
Abstract : Over the last century, girls in Africa, long ignored as sources of knowledge, have, nevertheless, engaged vocally and publicly in activism and artistic endeavors to express their visions and aspirations for a future society inclusive of their needs. Only recently have scholars begun to examine the complicated nature of girlhood in relation to capacity, competence, and knowledge layered with vulnerability and inexperience. In the last decade, the flourishing of girls' inventive acts of agency and their use of their own incisive voices have given impetus to the growing scholarship on girls' vibrant historical and current political, economic, creative, and cultural pursuits.